Estrategias didácticas constructivistas y la participación de los estudiantes en el proceso enseñanza aprendizaje de Ciencias Naturales. Año lectivo 2022-2023 - Rojas Dávila, Estrella Daniela (2023)
The constructivist didactic strategies promote the participation of students and allow the building of significative learning, for this, the research was made with the aim of << enhance the academic performance of students through the application of constructivist didactic strategies that improve the active participation in the development of the teaching and learning process in Natural Science of ninth year of basic education of “Adolfo Valarezo” educative unit, academic year 2022- 2023>>. Regarding the methodology, it was based on the inductive method identified through the direct observation, the low academic performance of students. It has a qualitative approach because the features of the learning environment in which the classroom process takes place are determined, with the use of the research and evaluation techniques such as: surveys, interviews and written tests. In turn, the investigation, according to the nature of information, corresponds to Participative Action Research (PAR), thus information about the problem is sought, in order to establish possible solutions. According to the temporal location, the research was of a cross-sectional type, since it was developed in a relatively short period of time that includes from the diagnosis to its completion. Once the research was concluded, it was determined that the application of constructivist didactic strategies is of relevant importance in the development of the teaching and learning process in Natural Science, because they encourage the active participation of students and enhance its academic performance. . Keywords: academic performance, teaching and learning process, constructivism, participative action research